Share price reactions to tariff imposition announcements during the first Trump administration - Wengerek, Sascha Tobias; Uhde, André; Hippert, Benjamin (Finance Research Letters)
This study analyzes the impact of tariff imposition announcements on the stock prices of 1,194 U.S. companies during the first Trump administration, using a unique sample of 4,624 announcements made by or against the U.S. between January 2018 and August 2019. We find that tariff announcements lead to negative (cumulative) average abnormal stock returns. These negative wealth effects occur regardless of whether the Trump administration imposes safeguard tariffs to protect domestic industries or foreign countries announce retaliatory tariffs. Moreover, the adverse impact is primarily driven by announcements involving China, with variations linked to sector-specific, tariff, trade, and firm characteristics.
Keywords: Geopolitical risk; Protectionism; Strategic trade policy; Tariffs; Trade conflict; U.S. – China trade war

Risk allocation through securitization – Evidence from non-performing loans - Wengerek, Sascha Tobias; Hippert, Benjamin; Uhde, André (The Quarterly Review of Economics and Finance)
Employing a unique and hand-collected sample of 648 true sale loan securitization transactions issued by 57 stock-listed banks across the EU-12 plus Switzerland over the period from 1997 to 2010, this paper empirically analyzes the relationship between true sale loan securitization and the issuing banks’ non-performing loans to total assets ratios. Overall, we provide evidence for a negative impact of securitization on NPL exposures suggesting that banks predominantly used securitization as an instrument of credit risk transfer and diversification. In addition, the analysis at hand reveals a time-sensitive relationship between securitization and NPL exposures. While we observe an even stronger NPL-reducing effect through securitization during the non-crisis periods, the effect reverses during and after the global financial crisis suggesting that banks were forced to provide credit enhancement and employ securitization as a funding management tool. Along with the results from a variety of sensitivity analyses our study provides important implications for the recent debate on reducing NPL exposures of European banks by revitalizing the European securitization market.
Keywords: European Banking; Non-performing Loans; Securitization

The relationship between announcements of complete mergers and acquisitions and acquirers' abnormal CDS spread changes - Hippert, Benjamin
Employing a sample of 492 merger and acquisition (M&A) announcements from 284 acquirers across North America and Europe between 2005 and 2018, this study analyzes the impact of M&A announcements on an acquirers abnormal CDS spread changes. We find that spreads from CDS which are written on acquirers increase by 310 bps during a symmetric five-day event window suggesting that investors expect an increase in the acquirers credit risk exposure due to M&As. Next to this baseline finding, we conduct a large variety of sensitivity analyses to gain more insight into the driving factors of the rising risk perception of CDS investors due to M&A announcements.
Keywords: credit default swaps; risk perception of CDS investors; mergers and acquisitions; event study

Portfolio Benefits of Adding Corporate Credit Default Swap Indices: Evidence from North America and Europe - Hippert, Benjamin; Uhde, André; Wengerek, Sascha Tobias (Review of Derivatives Research)
Employing main and sector-specific investment-grade CDS indices from the North American and European CDS market and performing mean-variance out-of-sample analyses for conservative and aggressive investors over the period from 2006 to 2014, this paper analyzes portfolio benefits of adding corporate CDS indices to a traditional financial portfolio consisting of stock and sovereign bond indices. As a baseline result, we initially find an increase in portfolio (downside) risk-diversification when adding CDS indices, which is observed irrespective of both CDS markets, investor-types and different sub-periods, including the global financial crisis and European sovereign debt crisis. In addition, the analysis reveals higher portfolio excess returns and performance in CDS index portfolios, however, these effects clearly differ between markets, investor-types and sub-periods. Overall, portfolio benefits of adding CDS indices mainly result from the fact that institutional investors replace sovereign bond indices rather than stock indices by CDS indices due to better risk-return characteristics. Our baseline findings remain robust under a variety of robustness checks. Results from sensitivity analyses provide further important implications for institutional investors with a strategic focus on a long-term conservative portfolio management.
Keywords: Corporate credit default swap indices; Mean-variance asset allocation; Out-of-sample portfolio optimization; Portfolio risk-diversification; Portfolio performance evaluation

Determinants of CDS trading on major banks - Hippert, Benjamin; Uhde, André; Wengerek, Sascha Tobias
Employing credit default swap (CDS) data for a sample of 52 major banks across 18 countries from 2008 to 2016, this paper investigates determinants of the outstanding net notional amount of CDS which are written on banks. We extend the current literature dealing with CDS trading by analyzing further CDS trading-specific, fundamental bank-specific as well as macroeconomic and institutional determinants with a focus on bank CDS trading. We find that, next to well-discussed determinants for corporate firms in the literature, especially a bank's tail risk, capital adequacy, loan portfolio and business model affect a bank's outstanding CDS net notional. This finding indicates that investors in the bank CDS market partly have a recourse to a fundamental analysis for their investment decision. Our study fills an important gap since empirical studies have solely focused on sovereign and corporate CDS yet. In addition, the analysis at hand provides important implications for both academics and practitioners since understanding the trading motives of bank CDS investors gives deeper insights into the still opaque CDS market.
Keywords: banking; outstanding CDS net notional; determinants of bank CDS trading

Determinants of CDS trading on major banks - Hippert, Benjamin; Uhde, André
Employing credit default swap (CDS) data for a sample of 52 major banks across 18 countries from 2008 to 2016, this paper investigates determinants of the outstanding net notional amount of CDS which are written on banks. We extend the current literature dealing with CDS trading by analyzing further CDS trading-specifi c, fundamental bank-speci fic as well as macroeconomic and institutional determinants with a focus on bank CDS trading. We fi nd that, next to well-discussed determinants for corporate firms in the literature, especially a bank's tail risk, capital adequacy, loan portfolio and business model affect a bank's outstanding CDS net notional. This finding indicates that investors in the bank CDS market partly have a recourse to a fundamental analysis for their investment decision. Our study fills an important gap since empirical studies have solely focused on sovereign and corporate CDS yet. In addition, the analysis at hand provides important implications for both academics and practitioners since understanding the trading motives of bank CDS investors gives deeper insights into the still opaque CDS market.
Keywords: banking; outstanding CDS net notional; determinants of bank CDS trading

The relationship between announcements of complete mergers and acquisitions and acquirers' abnormal CDS-Spread changes - Uhde, André; Hippert, Benjamin
Employing a sample of 492 merger and acquisition (M&A) announcements from 284 acquirers across North America and Europe between 2005 and 2018, this study analyzes the impact of M&A announcements on an acquirers abnormal CDS spread changes. We nd that spreads from CDS which are written on acquirers increase by 310 bps during a symmetric ve-day event window suggesting that investors expect an increase in the acquirers credit risk exposure due to M&As. Next to this baseline nding, we conduct a large variety of sensitivity analyses to gain more insight into the driving factors of the rising risk perception of CDS investors due to M&A announcements.
Keywords: credit default swaps; risk perception of CDS investors; mergers and acquisitions; event study